PENGARUH PENAMBAHAN EKSTRAK JAGUNG MANIS DAN AIR KELAPA PADA MEDIA MS SECARA IN VITRO TERHADAP INDUKSI TUNAS ADVENTIF BAWANG PUTIH (Allium sativum L.) - Marisa Gracia Bakara; Makhziah Makhziah; Guniarti Guniarti (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[SWEET CORN EXTRACT AND COCONUT WATER EFFECT TO INDUCE GARLIC (Allium sativum L.) ADVENTIST SHOOTS BY IN-VITRO CULTURE]. Garlic (Allium sativum L.) is one of the horticultural plants used daily for various uses. This study aims to determine the best extract concentration of sweet corn and coconut water and its interaction for induction garlic Adventist shoots (Allium sativum L.) var. Lumbu Hijau. The study was conducted at the Biotechnology Laboratory, Agriculture Faculty, UPN ”Veteran” East Java, in February – April 2021. The experimental design used was a factorial completely randomized design (CRD). The first factor is four levels of extract of sweet corn concentration (0, 50, 100, and 150 g/L), while the second factor is four levels of coconut water concentration (0, 50, 100, and 150 mL/L). The results showed that the extract of sweet corn concentration-time treatment increased the growing adventist shoots percentage, adventist shoots number, and adventist shoots size. The section of sweet corn concentration of 150 g/L increased the rate of growing adventist shoots, adventist shoots number, and adventist shoots size. The treatment of coconut water concentration and its interaction with the extract of sweet corn concentration is still not able for induction garlic adventist shoots (Allium sativum L.) of the var. Lumbu Hijau.